Pengaruh Sales Promotion dan E-Service Quality terhadap Impulse Buying pada E-Commerce Shopee - Maghfirotika At-Tamama Zidan; Rusdi Hidayat Nugroho (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to examine and analyze the effect of sale promotion and e-service quality on impulse buying on e-commerce Shopee. The population in this study is the people of Surabaya City who have shopped at Shopee e-commerce. The number of samples used in this study were 100 respondents. The sampling technique used is purposive sampling technique. This type of research uses quantitative. The results of this study indicate that sales promotion partially has no significant positive effect on impulse buying. E-Service Quality partially has a significant positive effect on Impulse Buying. Sales Promotion and E-service quality simultaneously have a significant positive effect on impulse buying. Keywords: Sales Promotion; E-Service Quality; Impulse Buying; Shopee